“Brightly Colored Magic and Weird Worlds”: Sylvia Plath’s Creation of Personae Through Her Visual Poetics - Sholto-Douglas, Alice (Department of English Language and Literature, 2020)
In this dissertation, I extend existing acknowledgments of the impact of Sylvia Plath’s visual arts training on her writing in order to argue that her painterly sensibilities are central to her character construction. Specifically, I contend that Plath draws upon a set of visual techniques, which I categorise as hallucinations, mental images, dreams, blurriness, and visual-to-verbal re-inscription. The ability to control subjective experience through the imagination, a philosophy Plath discusses in her journals, acts as a framework for her narratives, and visual techniques become, for Plath’s personae, a method of manipulating their experiences through a blurring of the divide between individual imagination and subjective reality. Plath’s visual techniques further function to represent her personae’s psychic interiority in ways that not only illustrate the limits to expression of the traditionally literary but also offer a means of overcoming these limits through an alternative system of meaning-making. Thus, her personae’s agency exists at the level of form, through self representation that is not stymied by the limitations of the written word, as well as at the level of narrative, through her personae’s control of experience. Moreover, because these visual techniques appear frequently in narratives that are preoccupied with a gendered power dynamic, I contend that we should understand Plath’s moments of resistance to textual tradition as enabling her personae’s escape from patriarchal limitations to freedom and selfexpression. While this recognition of the significance of Plath’s visual techniques should not necessarily constitute a panacea to the constraints of traditional language, it does offer a new way of reading Plath which acknowledges her painterly sensibilities as crucial to the way in which she gives her personae agency and writes back to her literary forefathers.